PENGARUH LOAN TO DEPOSITS RATIO, FIRM SIZE DAN DEBT TO ASSET RATIO TERHADAP RETURN ON ASSETS (Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2015-2019) - Ng Husin; Atika Purnamasari (JURNAL CAFETARIA, 2021)
This study aims to examine the effect of loan to deposits ratio, firm size and debt to asset ratio on return on assets in banking companies listed on the indonesia stock exchange 2015-2019. The research method used is hypothesis or causal testing. This study uses quantitative secondary data in the form of financial statements for the 2015-2019 period from banking companies listed on the indonesia stock exchange which were taken as a sample of 7 companies. The statistical analysis used in this study is multiple regression analysis, while the hypothesis testing used is the t test, r test, and the determinant coefficient (r2). The results of the research show that (1) Loan to deposits ratio has an effect on return on assets, (2) Firm size has an effect on return on assets, (3) Debt to asset ratio has an effect on return on assets, (4) Simultaneously loan to deposits ratio, firm size and debt to asset ratio has an effect on return on assets.